Food Insecurity During COVID-19 in Cameroon: Associated Factors and Adaptation Strategies - Atanase Yene; Sophie Michelle Eke Balla (Economies)
This study seeks to identify the factors driving household food insecurity in Cameroon during the COVID-19 pandemic, examine the effects of coping strategies on household resilience, and explore complementarities among these strategies. We used data from the COVID-19 panel surveys conducted by the National Institute of Statistics of Cameroon. Three models are estimated: an ordered logit model for food insecurity factors, a logit model for the impact of coping strategies, and a multivariate probit model for complementarities. The findings reveal that food insecurity is exacerbated by conflict, socio economic shocks (e.g., loss of employment, crop theft), and price hikes. About 28.59% of households are resilient, mainly due to past savings, cash transfers, free food, and in-kind transfers. The study emphasizes the importance of social and governmental support to mitigate food insecurity during crises, and underscores the need for monitoring socio-economic conditions during pandemics and other crises.